Extremely severe scoliosis, heterotopic ossification, and osteoarthritis in a three‐generation family with Crouzon syndrome carrying a mutant c.799T>C FGFR2. Issue 9 (18th July 2019) - Lin, Meina; Lu, Yongping; Sui, Yu; Zhao, Ning; Jin, Ying; Yi, Dongxu; Jiang, Miao
Abstract: Background: Crouzon syndrome is a rare and complex autosomal dominant craniosynostosis syndrome with a prevalence of approximately 1 in 60, 000 births. The typical features are craniosynostosis, proptosis, midfacial hypoplasia, and noncranial manifestations, including deformities in the cervical spine, elbow, and fingers. Crouzon syndrome is usually caused by pathogenic variants in the fibroblast growth factor receptor 2 ( FGFR2 ) gene. Methods: We reported a three‐generation family with Crouzon syndrome; the proband showed extremely severe limb abnormalities. The clinical features were obtained by physical examination and radiographic examination. Sanger sequencing of all 18 exons of FGFR2 was conducted to identify the disease‐causing mutation. Results: The proband was a 44‐year‐old man who showed characteristics of Crouzon syndrome, including craniofacial dysostosis, shallow orbits, proptosis, midface hypoplasia, beaked nose, strabismus, short superior lip, short stature, and neck injection. In addition to these typical characteristics, radiographic examination showed severe scoliosis, heterotopic ossification of the elbows, knee osteoarthritis, metacarpophalangeal joint valgus, collapse of the articular surface of the thumb metacarpal, knuckle ossification and fusion. Sanger sequencing identified a heterozygous pathogenic variant c.799T>C, p.(Ser267Pro) in exon 7 of FGFR2 in affected individuals. Conclusion: Crouzon syndrome in this three‐generation family was caused by c.799T>C FGFR2, and the patient showed a different phenotypic appearance from other Crouzon patients with c.799T>C FGFR2 . Abstract : we reported a three‐generation family of Crouzon syndrome caused by c.799T>C FGFR2, the proband showd extremly severe limb abnormalities, including severe scoliosis, heterotopic ossification of the elbows, knee joint osteoarthriti, metacarpoparthrosis, collapse of the articular surface of the thumb metacarpal, knuckle ossification and fusion.